Imbalance of Pro and Anti-Inflammatory Cytokines in Rheumatoid Arthritis in Iraqi Patients - Salih, Shakir M.; Adam, Sevki A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Rheumatoid arthritis is an autoimmune chronic inflammatory illness that affects the whole body and is characterized by non-articular involvement and inflammatory arthritis. It often develops by an interaction between genes and environmental factors. Objectives: This research was designed to investigate the effect of the imbalance between pro- and anti-inflammatory cytokines on patients with rheumatoid arthritis and in comparison, with healthy controls. Methods: Two groups (One"hundred) of patients with Rheumatoid arthritis (66female, 34 male) and 50 healthy control group (28female, 22 male)) were chosen in this study to investigate the effect of some laboratory parameters such as cytokines IL1, IL4, IL6, and IL20 measured by Enzyme-linked Immunosorbent Assay (ELISA)on patients visiting health institutions in the Al-Anbar Governorate / Iraq. The results of the laboratory tests of patients who had symptoms of rheumatoid arthritis were compared with the laboratory test results of healthy people for comparison. Results: The results indicated that the level of the cytokine IL1 increased significantly in the rheumatoid arthritis patient group (23.24 pg/mL) when compared with the group of healthy people (3.48 pg/mL). The results showed that the level of cytokine IL6 significantly increased in the rheumatoid arthritis patient group (50.66 pg/mL) compared to the healthy group (3.36 pg/mL). The results of cytokine IL20 significantly increased in the rheumatoid arthritis patient group (46.03 pg/mL) compared to the healthy group (15.02 pg/mL). The cytokine IL4 level showed a significant increase within the rheumatoid arthritis patient group (51.95 pg/mL) compared with the healthy people group (9.09 pg/mL). Conclusion: The levels of cytokines IL1, IL4, IL6, and IL20 increased significantly in the rheumatoid arthritis patient group compared to the group of healthy people.